Sistem Pendukung Keputusan Pemilihan Penyedia Barang dan jasa (Jasa Lainnya) pada Sekretariat DPRD Prov Kepri menggunakan Metode Simple Additive Weighting - Manihuruk, Wan Hendra; Irvandi, Weldy (Jurnal Bangkit Indonesia, 2024)
Choosing a provider of goods/services in a government is very difficult because it requires providers of goods/services that meet the requirements. work unit organizing procurement of goods/services established by Ministries/Institutions/Universities/ BUMN and Regional Governments to facilitate Procurement Officials in carrying out procurement of other goods/services in government with a system, to create transparency, efficiency, and effectiveness as well as accountability in selecting providers other goods and services through the decision support system for goods/service providers at the DPRD Secretariat of Riau Islands Province. To find the weighted sum of the performance ratings for each alternative on all criteria. Keywords— Selection of goods/service providers, Simple Additive Weighting, Decision Support System, administrative qualifications, technical qualifications and price offers.